TEKNOLOGI DAN PERTUMBUHAN EKONOMI - Setyowati, Eni (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2001)
People efficiently aware that exploitation of development technology gives significant economy advantage. This such of awareness supports the development of competition in technology innovation and the competition of exploitation technology to reach bigger economy advantage. The economical impact of the exploitation of technology constitutes occurring of management and organization transition in various companies both of a capital intensive and labour intensive. The writer also analyses an opinion of neoclassic economist about advancement of technology. The empirical analysis points out that national production (Y) is not only caused by capital development (K) and the growth of employee (L), but also caused by the other factor, which at the beginning are considered as residual factor. It is called Total Factor Productivity (TFP).